PENGARUH EXECUTIVE CHARACTERISTICS, FIRM SIZE DAN SALES GROWTH TERHADAP TAX AVOIDANCE - Stefanny, Yuniarwati (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to obtain empirical evidence about the effects of executive characteristics, firm size and sales growth ontax avoidance of the manufacturing companies listed in the Indonesia Stock Exchange in the period of 2015-2018. The research is conducted by taking 67 samples using purposive sampling method. The result of this research shows that all the independent variables have effects on tax avoidance (ETR) simultaneously (F test). The t test results showed that sales growth (GOS) has a significant negative effect on tax avoidance (ETR), while firm size (SIZE) and sales growth (GOS) have no positive significant effect on tax avoidance (ETR).